The effects of ultra-selective beta1-antagonism on the metabolic and cytokine profile in septic shock patients receiving noradrenaline: a sub-investigation from the STRESS-L Randomised Study - Jarrod L. Thomas; Kirsty C. McGee; Anower Hossain; Gavin D. Perkins; Anthony C. Gordon; Duncan Young; Danny McAuley; Mervyn Singer; Ranjit Lall; Tina Kramaric; Janet M. Lord; Tony Whitehouse; et al. (Intensive Care Medicine Experimental)
Abstract Purpose The landiolol and organ failure in patients with septic shock (STRESS-L study) included a pre-planned sub-study to assess the effect of landiolol treatment on inflammatory and metabolomic markers. Methods Samples collected from 91 patients randomised to STRESS-L were profiled for immune and metabolomic markers. A panel of pro- and anti-inflammatory cytokines were measured through commercially acquired multiplex Luminex assays and statistically analysed by individual and cluster-level analysis (patient). Metabolite fingerprinting was carried out by flow infusion electrospray ionisation high-resolution mass spectrometry and metabolomic data were analysed using the R-based platform MetaboAnalyst. The metabolites were identified using DIMEdb (dimedb.ibers.aber.ac.uk) from their mass/charge ratios. These metabolomic data were also re-analysed using individual and cluster-level analysis. The individual-level models were adjusted for confounders, such as age, sex, noradrenaline dosage and patient (random effect). Results Analysis was undertaken at cluster- and individual-level. There were no significant differences in cytokine concentration level between trial arms nor survivors and non-survivors over the duration of the observations from day 1 to day 4. Metabolomic analysis showed some separation in the levels of ceramides and cardiolipins between those who survived and those who died. Following adjusted analysis for confounders, plasma metabolite concentrations remained statistically different between landiolol and standard care arms for succinic acid, l-tryptophan, l-alanine, 2,2,2-trichloroethanol, lactic acid and d-glucose. Conclusions In a study of ICU patients with established septic shock and a tachycardia, landiolol treatment used to reduce the heart rate from above 95 to a range between 80 and 94 beats per minute did not induce significant cytokine changes. d-Glucose, lactic acid, succinic acid, l-alanine, l-tryptophan and trichloroethanol were pathways that may merit further investigation. Trial Registration: EU Clinical Trials Register Eudra CT: 2017-001785-14 ( https://www.clinicaltrialsregister.eu/ctr-search/trial/2017-001785-14/GB ); ISRCTN registry Identifier: ISRCTN12600919 ( https://www.isrctn.com/ISRCTN12600919 ).